Optimizing the linear quadratic minimum-time problem for discrete distributed systems - Rachik, Mostafa; Abdelhak, Ahmed (Zielona Góra: Uniwersytet Zielonogórski)
With reference to the work of Verriest and Lewis (1991) on continuous finite-dimensional systems, the linear quadratic minimum-time problem is considered for discrete distributed systems and discrete distributed time delay systems. We treat the problem in two variants, with fixed and free end points. We consider a cost functional J which includes time, energy and precision terms, and then we investigate the optimal pair (N, u) which minimizes J.
Keywords: discrete distributed systems; time delay systems; minimum time; optimal control